Reading Skills in Preschool and School-aged Children with Unilateral Cochlear Implants in Iran: A Narrative Review - Zahra Jeddi; Shaghayegh Omidvar; Afsaneh Doosti; Seyedeh Zahra Fakhr Hosseini (Shiraz University of Medical Sciences, 2022)
Background: The acquisition of reading skills is one the most important challenges a cochlear implanted child faces in his/her life. Although cochlearimplants can improve speech, language, and reading skills, some childrencontinue to experience reading difficulties. Some studies have reviewed thereading skills in English-speaking children with cochlear implants; however,language and cultural discrepancies may result in diverse aural rehabilitationprograms and varying effects of factors on reading in these children. The aimof the present study is to review evidence regarding reading skills, includingphonological awareness, reading comprehension, vocabulary, and story retellingin preschool and school-aged children with unilateral cochlear implants in Iran.Results: Overall, the findings of studies in this area suggest that Persianspeakingpreschool and school-aged children with unilateral cochlear implantsshow worse reading performance compared with their normal hearing peers.Conclusion: Impaired reading skills in children with cochlear implantsnecessitates the identification of reading problems and targeted auralrehabilitation programs to improve reading skills in these children. Futurestudies over longer periods are necessary in order to determine the readingdevelopmental trajectory of children with cochlear implants in Iran. In addition,investigating the precise role of underpinning abilities such as language andhearing skills in reading development can help children with cochlear implantsachieve age-appropriate reading skills.